Data acquisition system for Kenyir hydroelectric power plant. - Mansor, Mohamad Isa; Ghows Khan, Osman Khan (1986)
The national electricity board of the States of Malaya has been using the state-of-the-art technology for process control at its power generating stations and control centres. Kenyir Hydroelectric Power Station, which is located in the state of Terengganu and has been constructed and commissioned recently, is one of them. It has a maximum generating capacity of 400 MW from 4 generators and supplies power to the national grid which operates on 275 kV and 132 kV. A data acquisition system will be installed to assist the operators in running the plant efficiently and safely. Functionlly, the system will be provide facilities for monitoring parameters, supervise measurands, man-machine interface, and system development. Parameters monitored are alarms points (1400), indications (250 single and double points), and measurands both digital and analog types. Man-machine interface function is to display status, log events and operator's actions, generate reports, provide trending and data amendment. System development provide facilities for sftware development and maintenance. The system is implemented using the Bailey N 9090 system which employs a distributed processing concept. Plant inputs are connected to the loop, to which the Management Command System is also connected. The system is provided initially for the station use only. Future development will include a linkage between this system to that of an upstream Station in Ulu Terengganu for the purpose of remotely controlling the station.